2021
DOI: 10.1097/brs.0000000000004137
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Medial Safe Zone for C2 Pedicle Instrumentation

Abstract: Study Design. Retrospective observational study.Objective. The aim of this study was to investigate the spinal cord safety margins for C2 instrumentation. Summary of Background Data. Intraoperative spinal cord injury during C2 spine surgery is a rare, but potentially lifethreatening complication. Preoperative planning for C2 instrumentation mainly focuses on C2 pedicle bony dimensions on CT and the vertebral artery location and few studies have evaluated C2 spinal cord safety margins. Methods. We measured two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…In our study, the mean MPD of BI patients was 2.09 mm. Therefore, a breach of the medial wall of the pedicle up to 50% of the screw diameter is usually safe, similar to the expressed by Sciubba et al 17 However, the MPD of 3.53 mm measured by Bydon et al and 2.9 mm by Lee et al and the MPD and MPSC of 5.6 mm and 10.1 mm, respectively measured by Chiapparelli et al , are larger than the measures made for our cohort 13,20,24 . We believe that such differences are due to the following: BI patients often have Chiari malformation, which may enlarge the dura and spinal cord, leading to a reduction in MPD and MPSC; the anteroposterior diameter of the spinal canal is smaller than normal in BI patients, 3 which may cause the dura to expand laterally, leading to a reduction in MPD; compared with the studies of Bydon et al and Chiapparelli et al, the results of Lee et al are closer to this study, indicating that racial differences may also be an important factor 13,20,24 …”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In our study, the mean MPD of BI patients was 2.09 mm. Therefore, a breach of the medial wall of the pedicle up to 50% of the screw diameter is usually safe, similar to the expressed by Sciubba et al 17 However, the MPD of 3.53 mm measured by Bydon et al and 2.9 mm by Lee et al and the MPD and MPSC of 5.6 mm and 10.1 mm, respectively measured by Chiapparelli et al , are larger than the measures made for our cohort 13,20,24 . We believe that such differences are due to the following: BI patients often have Chiari malformation, which may enlarge the dura and spinal cord, leading to a reduction in MPD and MPSC; the anteroposterior diameter of the spinal canal is smaller than normal in BI patients, 3 which may cause the dura to expand laterally, leading to a reduction in MPD; compared with the studies of Bydon et al and Chiapparelli et al, the results of Lee et al are closer to this study, indicating that racial differences may also be an important factor 13,20,24 …”
Section: Discussionsupporting
confidence: 79%
“…In clinical practice, encroachments of the transverse foramen (TF) or spinal canal caused by C2PS occurs sometimes, especially more frequently in BI patients with and without high-riding VA, 12 while neurovascular complications are rare 13–18 . Besides, the medial and lateral buffer space of the C2 pedicle can be observed on imaging 19–21 . Another viable option can consist of C2PS fixation with a medial/lateral “in-out-in” technique, deliberately breaching the pedicle cortex to apply screws to patients with narrowed pedicles and provide three-column fixation 22–24 .…”
mentioning
confidence: 99%
“…Thon et al found high rates of healing with the use of a bio-inductive collagen patch scaffold during the repair of massive rotator cuff tears [ 23 ]. Recent studies have also found lower failure rates in small and medium-sized tears augmented with PRP during the repair [ 24 , 25 ]. Additionally, cBMA has been found to significantly decrease rotator cuff repair failure rates [ 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%